2016
DOI: 10.1186/s13293-016-0113-7
|View full text |Cite
|
Sign up to set email alerts
|

Sexual dimorphism in the mast cell transcriptome and the pathophysiological responses to immunological and psychological stress

Abstract: BackgroundBiological sex plays a prominent role in the prevalence and severity of a number of important stress-related gastrointestinal and immune-related diseases including IBS and allergy/anaphylaxis. Despite the establishment of sex differences in these diseases, the underlying mechanisms contributing to sex differences remain poorly understood. The objective of this study was to define the role of biological sex on mast cells (MCs), an innate immune cell central to the pathophysiology of many GI and allerg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
58
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 96 publications
6
58
0
Order By: Relevance
“…Given the present findings and our previous studies in mice and rats, female mast cells possess the ability to synthesize, store and release more mast cell mediators compared with male MCs (48), the enhanced tryptase release could be a result of increased tryptase content in female EWS mast cells. In addition differences in adult sex hormones, such as increased estrogen in female pigs or reduced androgens in Male-C pigs could have contributed to these changes.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Given the present findings and our previous studies in mice and rats, female mast cells possess the ability to synthesize, store and release more mast cell mediators compared with male MCs (48), the enhanced tryptase release could be a result of increased tryptase content in female EWS mast cells. In addition differences in adult sex hormones, such as increased estrogen in female pigs or reduced androgens in Male-C pigs could have contributed to these changes.…”
Section: Discussionsupporting
confidence: 78%
“…Therefore, an enhanced release of MC tryptase in EWS females pigs could have artificially reduced the number of mast cells in the intestinal tissues in female pigs. We have previously shown that mast cell tryptase and chymase expression can differ significantly in chronically stressed pigs (54) and that female mast cells obtained from rat and mice contain higher amounts of intracellular mediators at baseline (non-stressed conditions) compared with sexually mature intact males (48) suggesting the composition of mediators in female and male mast cells are different and can change in response to stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mast cell numbers increase in specific brain regions in both male and female rodents when exposed to sexually receptive stimuli of the other sex 63,64 . Furthermore, the transcriptome of peripheral mast cells is markedly different in males and females 65 . Mast cells have not yet been implicated directly in brain sexual differentiation, but, given their involvement in reproductive responses, the potential for such a role is high.…”
Section: Mechanisms Of Sexual Differentiationmentioning
confidence: 99%
“…Additionally, these expression differences can lead to skewed disease risk between sexes [19]. Differences in gene expression between sexes has been shown to be relevant in human neurological diseases [15] and immune diseases, such as irritable bowel syndrome and allergy [20]. While gene expression differences between sexes can contribute to disease, there is also evidence that sexually dimorphic gene expression patterns are evolutionarily conserved and therefore also important to phenotypic differences between sexes [21].…”
Section: Introductionmentioning
confidence: 99%